2023
DOI: 10.1093/beheco/arad067
|View full text |Cite
|
Sign up to set email alerts
|

Food supply and provisioning behavior of parents: Are small hoopoe nestlings condemned to die?

Paula Ferrer-Pereira,
Ester Martínez-Renau,
Manuel Martín-Vivaldi
et al.

Abstract: Parents might use signals of need or of quality to decide food provisioning among their offspring, while the use of one or another signal might depend on food availability. Begging success of nestlings of different quality (i.e., body size) would also depend on food availability, and we here explore the effect of experimental food supply in begging success of nestlings and in provisioning of female hoopoes (Upupa epops), a species with extreme hatching asynchrony and nestlings size hierarchy. We video-recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Functions of parental overproduction are not mutually exclusive, yet only a few studies, mostly in temperate birds, have examined and quantified them under a multiple-hypothesis approach ( Mock and Parker 1986 ; Wiebe 1996 ; Forbes et al 2002 ; Humphries et al 2006 ; Ferrer-Pereira et al 2023 ). These documented both resource-tracking and insurance benefits of marginal young to adults’ reproductive success and showed that their magnitude and relative importance could vary across and within species depending on extrinsic and intrinsic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Functions of parental overproduction are not mutually exclusive, yet only a few studies, mostly in temperate birds, have examined and quantified them under a multiple-hypothesis approach ( Mock and Parker 1986 ; Wiebe 1996 ; Forbes et al 2002 ; Humphries et al 2006 ; Ferrer-Pereira et al 2023 ). These documented both resource-tracking and insurance benefits of marginal young to adults’ reproductive success and showed that their magnitude and relative importance could vary across and within species depending on extrinsic and intrinsic conditions.…”
Section: Introductionmentioning
confidence: 99%